2015
DOI: 10.1111/eos.12195
|View full text |Cite
|
Sign up to set email alerts
|

Dental treatment need and dental general anesthetics among preschool‐age children with cleft lip and palate in northern Finland

Abstract: Cleft lip and palate incidence is high in northern Finland. This study aimed to investigate the proportion of children in need of restorative dental treatment among cleft lip and palate patients in northern Finland, as well as their need for dental treatment under general anesthesia. The records of 183 cleft lip and palate patients, treated in Oulu University Hospital from 1997 to 2013, were reviewed. Data on dental caries were analyzed in association with cleft type, considering also the presence of syndromes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
2
17
0
3
Order By: Relevance
“…Comparable to the results of previous studies (Lehtonen et al, 2015;Solanki et al, 2016), most subjects in the current study had no previous dental history. This finding indicated that the recorded visit was the subject's first dental visit, which is suggestive of the parents' poor understanding of primary teeth function and the importance of maintaining dentition.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…Comparable to the results of previous studies (Lehtonen et al, 2015;Solanki et al, 2016), most subjects in the current study had no previous dental history. This finding indicated that the recorded visit was the subject's first dental visit, which is suggestive of the parents' poor understanding of primary teeth function and the importance of maintaining dentition.…”
Section: Methodssupporting
confidence: 76%
“…The subjects in the current study had badly broken down and decayed primary molars due to ECC, and they required pulp therapy to allow the teeth to be retained inside the mouth and to function as a space maintainer while awaiting exfoliation. Hence, SSCs were used to ensure that the tooth function could be restored, and to avoid repeated treatment under GA, and to achieve better longterm outcome (Abdul Karim et al, 2008;Lehtonen et al, 2015). Another material of choice to restore primary molars is GIC, which has the advantage of releasing fluoride, calcium, and phosphate ions (Abdul Karim et al, 2008), and a tooth coloured material that provides good aesthetic results.…”
Section: Discussionmentioning
confidence: 99%
“…In our population, this was higher (at 54%) and this may represent an underestimate as children with missing teeth could not be scored. Other studies have reported a higher prevalence of DDE in children with clefts . The aetiology of DDE is not entirely clear, but it has been associated with poor maternal health during pregnancy, pre‐term birth and hospitalization in the first year of life; the majority of these children would have been admitted to hospital in their first year of life for cleft repair operations.…”
Section: Discussionmentioning
confidence: 99%
“…31 These findings are supported by other studies. [32][33][34] Just over half of studies in this review reported on cleft type and this potential variable could not be explored further. Only three studies included syndromic children.…”
Section: Factors That Could Confound or Modify Riskmentioning
confidence: 99%